SIRT1 regulates macrophage self‐renewal. (12th July 2017) - Imperatore, Francesco; Maurizio, Julien; Vargas Aguilar, Stephanie; Busch, Clara J; Favret, Jérémy; Kowenz‐Leutz, Elisabeth; Cathou, Wilfried; Gentek, Rebecca; Perrin, Pierre; Leutz, Achim; Berruyer, Carole; Sieweke, Michael H
Abstract: Mature differentiated macrophages can self‐maintain by local proliferation in tissues and can be extensively expanded in culture under specific conditions, but the mechanisms of this phenomenon remain only partially defined. Here, we show that SIRT1, an evolutionary conserved regulator of life span, positively affects macrophage self‐renewal ability in vitro and in vivo . Overexpression of SIRT1 during bone marrow‐derived macrophage differentiation increased their proliferative capacity. Conversely, decrease of SIRT1 expression by shRNA inactivation, CRISPR/Cas9 mediated deletion and pharmacological inhibition restricted macrophage self‐renewal in culture. Furthermore, pharmacological SIRT1 inhibition in vivo reduced steady state and cytokine‐induced proliferation of alveolar and peritoneal macrophages. Mechanistically, SIRT1 inhibition negatively regulated G1/S transition, cell cycle progression and a network of self‐renewal genes. This included inhibition of E2F1 and Myc and concomitant activation of FoxO1, SIRT1 targets mediating cell cycle progression and stress response, respectively. Our findings indicate that SIRT1 is a key regulator of macrophage self‐renewal that integrates cell cycle and longevity pathways. This suggests that macrophage self‐renewal might be a relevant parameter of ageing. Synopsis: Sirtuin1 (SIRT1), a mammalian homolog of yeast Silent Information Regulator 2 (Sir2) and evolutionary conserved regulator of life span, positively affects self‐renewal ability of macrophages in vitro and in vivo . SIRT1 is a key regulator of macrophage self‐renewal that integrates cell cycle and longevity pathways. Overexpression of SIRT1 in bone‐marrow derived macrophages increases their proliferative capacity. Decrease of SIRT1 expression by shRNA inactivation, CRISPR/Cas9 mediated deletion and pharmacological inhibition by nicotinamide or inauhzin, restricts macrophage self‐renewal. SIRT1 inhibition limits alveolar and peritoneal macrophages proliferation in vivo . In macrophages, SIRT1 is required for cell cycle progression and self renewal gene activity, like E2F1 and Myc, but inhibits stress response genes like FOXO1. Abstract : The life span regulator SIRT1 controls a transcriptional network for macrophage cell cycle progression and stress responses, implying macrophage self‐renewal as a potential parameter of aging.